PENGARUH TINGKAT SALINITAS MEDIA TUMBUH TERHADAP PERTUMBUHAN DAN HASIL TIGA VARIETAS KACANG HIJAU (Vigna radiata L.) - Oematan, Shirly Seahan; Arsa, I G.B. Adwita; Due, Erminilda Fatmawati; Roefaida, Effy; Bunga, Widasari (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
This research was carried out at the Integrated Field Laboratory for Archipelago Dry Land, Faculty of Agriculture, University of Nusa Cendana from July to September 2022. The purpose of this study was to determine the effect of salinity level of growing media on the growth and yield of three mung bean varieties (Vigna radiata L.). The design used in this study was a Completely Randomized Design (CRD) consisting of two factors. The first factor is factor salinity level (G) which consists of 4 treatment levels, namely 0, 10, 20, 30 g NaCl/ kg soil and the second factor is variety (V) which consists of 3 treatment levels, namely Local Flores, Fore Belu. ), and Vima-3 in order to obtain 12 treatment combinations, with four replications so that there were 48 experimental units. The parameters observed in this study were plant height, number of leaves, number of pods, pod weight, weight of 100 seeds and seed yield per plant. The results showed that the salinity level treatment had a significant effect on all observation parameters. While the varietal treatment had a significant effect on plant height at 28 and 56 DAP, number of leaves at 28 DAP and weight of 100 seeds. There was an interaction between salinity level and variety on the number of leaves at 28 DAP. The best variety for all levels of salinity is Fore Belu and the variety that is tolerant to high level of salinity is Vima-3 (V3).